Throughput Analysis on LTE Network for Multicast D2D System - Fardiansyah Adami (LPPM Politeknik Aceh Selatan, 2019)
One of the features applied to fifth generation (5G) technology is Device-to-Device (D2D) communication. The D2D communication can occur directly without going through evolved Node B (eNB). Therefore, that it can reduce traffic density on cellular network communications. However, the application of D2D communication has constrained by the limited transmission distance and multi-user service at the same source. Modelling and simulating the LTE D2D multicast network using software is an effectively and efficiently ways for analyzing mac throughput. The testing of network aims to observe and to analyze the mac throughput using two parameters, the transmission distance and the number of users, based on the utilization of the Channel Quality Indicator (CQI) index. The number of user is 20 and distance is 25 meters then mac throughput in index CQI 13 greater than CQI 4 and CQI 7 is 2150.14 Kbps. But the number of user is 20 and distance is 150 meters then CQI 13 smaller than CQI 4 and CQI 7 is 271.22 Kbps. The result of simulation shows that both distance and the number of user have influence mac throughput. The selection of CQI index is the most important factor to maintain the transmission quality and mac throughput.